Seroprevalence and associated risk factors for foot and mouth disease virus seropositivity in cattle in selected districts of Gamo zone, Southern Ethiopia - Shurbe, Mesfin; Simeon, Bekahegn; Seyoum, Wasihun; Muluneh, Ayelech; Tora, Ephrem; Abayneh, Edget (Frontiers in Veterinary Science, 2022)
Background Foot and mouth disease (FMD) is a highly contagious viral disease of cloven-hoofed animals, which hampers livestock production and productivity in Ethiopia. This cross-sectional study was conducted from January to December 2021 to estimate the seroprevalence of FMD in cattle and to assess farmers' knowledge about the disease in selected districts of the Gamo zone. Three districts and two kebeles (smallest administrative division) from each district were purposively sampled using a simple random sampling technique to select individual animals from each kebeles. A total of 384 sera samples were collected, and concurrently, 100 farmers were interviewed. The samples were tested for antibodies against nonstructural proteins of the FMD virus using a 3ABC enzyme-linked immunosorbent assay (ELISA). Univariable and multivariable logistic regressions were used to analyze FMD-associated risk factors. Result The questionnaire survey result revealed that among the interviewed farmers, 66% of farmers had knowledge about the disease, and 28% of farmers reported having a case of FMD in at least one cattle in their farm in the previous 6 months. The overall seroprevalence of FMD in cattle was 26.8%. The multivariable logistic regression revealed that age, breed, and agroecology had a significant association with seropositivity. Higher seroprevalence (64.57%) was observed in lowland, followed by midland (9.30%) and highland (5.88%). Study animals from lowland areas were 9.26 times more likely to be seropositive (OR = 9.26, CI = 2.22–38.62) for FMD than highland animals. Also, adult animals were 9.01 times (OR = 9.01, CI = 3.18–25.53) more likely to be seropositive for the disease than young animals. The multivariable logistic regression revealed that crossbreeds have an 84.7% (OR = 0.153, CI = 0.028–0.82) lower likelihood to be seropositive to FMD than local breeds. Conclusion This study result confirms that FMD is highly prevalent in the study area, and farmers' knowledge regarding disease transmission and vaccine availability is minimal. Hence the regional concerned bodies should implement FMD vaccination campaigns and create awareness for smallholder farmers regarding the disease transmission, FMD vaccine schedule, and vaccination importance.